(untitled) (Experimental biology, 2025)
The article considers the impact of various disturbance factors on the composition and structure of vegetation of the desert part of the Syrdarya river valley within Kyzylorda region. Studies conducted in 2015-2023 revealed a wide degradation of vegetation cover caused by intensive grazing, irrational rice cultivation, anthropogenic and transport impact, as well as other forms of anthropogenic load. The most destroyed areas are characterised by a decrease in species richness, displacement of fodder and ecologically valuable species by weedy and toxic plants such as Peganum harmala, Zygophyllum fabago, Pseudosophora alopecuroides and others. The conclusions of the article emphasize the need to take into account the degree of disturbance when developing programmes for rehabilitation and sustainable use of degraded lands in arid climate conditions.